2018
DOI: 10.1590/s0004-2803.201800000-66
|View full text |Cite
|
Sign up to set email alerts
|

Association of Promoter Region Polymorphisms of Interleukin-10 Gene With Susceptibility to Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Background -Several epidemiological studies have investigated the association of promoter region polymorphisms of Interleukin-10 (IL-10) gene with colorectal cancer (CRC), while the conclusion is still conflicting and inconclusive. Objective -We conducted this meta-analysis to evaluate the association of promoter region polymorphisms of IL-10 with CRC. Methods -Eligible articles were identified by a search of several bibliographic databases for the period up to March 15, 2018. The strength of the association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Therefore, the assessment of heterogeneity is necessary, as high heterogeneity could be caused by the fact that there are actually two or more subgroups of studies present in the data, which have a different true effect. According to our previous metaanalyses, we suggested that heterogeneity might be due to differences in study design, sample size, genotyping methods, disease heterogeneity, and to the different roles played by gene-gene and gene-environment interactions (Aflatoonian et al, 2019a;Mirjalili et al, 2018;Moghimi et al, 2019Moghimi et al, , 2018. Moreover, after subgroup an analysis, heterogeneity was obviously decreased in Asians; however, the corresponding pooled ORs were not materially altered after deleting these studies, indicating that our results were statistically robust.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the assessment of heterogeneity is necessary, as high heterogeneity could be caused by the fact that there are actually two or more subgroups of studies present in the data, which have a different true effect. According to our previous metaanalyses, we suggested that heterogeneity might be due to differences in study design, sample size, genotyping methods, disease heterogeneity, and to the different roles played by gene-gene and gene-environment interactions (Aflatoonian et al, 2019a;Mirjalili et al, 2018;Moghimi et al, 2019Moghimi et al, , 2018. Moreover, after subgroup an analysis, heterogeneity was obviously decreased in Asians; however, the corresponding pooled ORs were not materially altered after deleting these studies, indicating that our results were statistically robust.…”
Section: Discussionsupporting
confidence: 51%
“…Also, several findings were reporting no (significant difference) association of IL10 − 1082G/A SNP with various types of cancers as a non-Hodgkin lymphoma [76], cervical cancer [77], gastric cancer [78], colorectal cancer [79], prostate cancer [80], breast cancer [23], and diffuse large B cell lymphoma DLBCL [67].…”
Section: Discussionmentioning
confidence: 99%
“…The IL-10 promoter is highly polymorphic [17][18][19][20], and three single nucleotide polymorphisms (SNPs) at positions -1082G>A, -819C>T and -592C>A polymorphisms within the promoter region have been shown to correlate with IL-10 production (22,24,25). To date, several genetic epidemiology studies have assessed the association between IL-10 -1082G>A, -819C>T and -592C>A polymorphisms and pediatric asthma in different populations (26,27).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%